Immunocytologic identification of serous and mucinous cystadenocarcinoma types of ovarian carcinoma that have metastasised to serous fluids - (:unkn) unknown (Turkiye Klinikleri, 2009)
Objective: Most cases of neoplastic deaths in females are due to ovarian carcinoma. Ovarian carcinomas are generally primary tumors and they cause plevral, peritoneal and pericardial effusion after metastasis. Subclassification of ovarian carcinoma is important both biologically and therapeutically. We aimed to demonstrate the specificity of several reactives in the serous fluids in detection of serous and mucinous metastatic ovarian adenocarcinomas. Material and Methods: Eight hundred fifty serous fluid specimens admitted to Hannover Cytopathology Laboratory with suspected ovarian carcinoma metastasis were stained with May Grünwald-Giemsa and 127 of them were diagnosed as metastatic carcinoma. In order to detect the primary site, alkaline phosphatase (ALP), cancer antigen 125 (CA 125) and cancer antigen 15-3 (CA 15-3) reactives were applied to these 127 serous fluids and 116 of them were diagnosed as ovarian carcinoma metastasis. For differentiation of the serous and the mucinous types, alcian blue (AB), vimentin (VIM) and cytokeratin 20 (CK20) reactives were applied to these samples. Results: AB and CK20 positive reactivities were found to be more significant in mucinous cystadenocarcinomas than in serous cystadenocarcinomas (93 vs. 7% for AB and 95.5 vs. 4.5% for CK20, respectively p< 0.001). However, VIM was found to reflect negative reactivity in mucinous cystadenocarcinomas (92.3%) comparing with serous cystadenocarcinomas (7.7 %) (p< 0.001). Conclusion: Positive AB and CK20 reactivity has a higher predictive value for detection of mucinous cystadenocarcinomas in patients with serous fluid metastasis, whereas negative VIM reactivity may have similar importance for cytological differentiation of serous ovarian cystadenocarcinomas. Copyright © 2009 by Türkiye Klinikleri.
Keywords: Adenocarcinoma; Immunocytochemistry; Ovarian carcinoma; Pleura-ascites-pericardial fluid; Serous-mucinous identification